2021
DOI: 10.1186/s12911-021-01596-6
|View full text |Cite
|
Sign up to set email alerts
|

Compliance with medical recommendations depending on the use of artificial intelligence as a diagnostic method

Abstract: Background Advanced analytics, such as artificial intelligence (AI), increasingly gain relevance in medicine. However, patients’ responses to the involvement of AI in the care process remains largely unclear. The study aims to explore whether individuals were more likely to follow a recommendation when a physician used AI in the diagnostic process considering a highly (vs. less) severe disease compared to when the physician did not use AI or when AI fully replaced the physician. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(14 citation statements)
references
References 44 publications
1
11
0
Order By: Relevance
“…Human interaction in addition to AI use was considered critical for the experience of high-quality care 22 . The importance of human interactions is further supported by evidence showing that patients' compliance was higher for physicians and for physicians using AI compared to an AI-system alone 8 . This so called augmented intelligence emphasizes that AI enhances or assists human intelligence rather than replacing it, expressing the importance of symbiosis between humans and AI 16,23,24 .…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…Human interaction in addition to AI use was considered critical for the experience of high-quality care 22 . The importance of human interactions is further supported by evidence showing that patients' compliance was higher for physicians and for physicians using AI compared to an AI-system alone 8 . This so called augmented intelligence emphasizes that AI enhances or assists human intelligence rather than replacing it, expressing the importance of symbiosis between humans and AI 16,23,24 .…”
Section: Discussionmentioning
confidence: 95%
“…Examples within gastrointestinal (GI) endoscopy include detection and classification of colorectal lesions 3 , differentiation between superficial and deep invasive colorectal cancer 4 , disease severity scoring of inflammatory bowel diseases 5 , localizing blind spots during esophagogastroduodenoscopy 6 , and detecting Barrett's neoplasia 7 . Some of these AI-systems diagnose diseases with expert-level accuracy or even outperform human experts [7][8][9] .AI-based systems can also be used in personalized healthcare 10 . Labovitz et al (2017) showed that AI is helpful in improving compliance to therapy 11 .…”
mentioning
confidence: 99%
“…The concept of social presence can explain this result. 51 Experts believe that technological singularity—a future point in time at which computers will exhibit superhuman intelligence—cannot be achieved without empathy in healthcare, leading to the development of concepts like artificial empathy or empathy-driven digital tools. 47,52,53 Personalized healthcare is only possible if it is responsive to patient needs, with an emphasis on the physician's perception of (past) medical history and physical examination.…”
Section: Discussionmentioning
confidence: 99%
“…(50) Furthermore, there is hesitancy among patients and physicians to use computer-based recommender systems that lack the art of human element of medicine and intend to base clinical decisions on computer algorithms. (51,52) Physicians possess accumulated clinical wisdom on the patient characteristics that are relevant when making treatment decisions. (19,53,54) Because of this unique knowledge, physicians are better positioned to phenotype or de ne reference classes of patients.…”
Section: Discussionmentioning
confidence: 99%
“…(7,13,21,(23)(24)(25) Physicians possess accumulated clinical wisdom on the patient characteristics that are relevant when making treatment decisions. 19,51,52 Because of this unique knowledge, we believe physicians are best positioned to de ne reference classes of similar patients. ICSCEDIT takes a physician-driven approach to refence class selection.…”
Section: Introductionmentioning
confidence: 99%